2002
DOI: 10.1034/j.1600-051x.2002.290104.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone loss in periodontal disease and polymorphism of N‐acetyltransferase (NAT2)

Abstract: The data suggest that the slow acetylator phenotype may be associated with a higher risk of periodontitis, especially in smokers. Possible explanations regarding the mechanism are discussed; however, such attempts are highly speculative at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…This is synonymous to stating that for severe bone loss to occur in a smoker, the smoker has to be susceptible. Unfortunately, little is presently known bout what makes a smoker susceptible (Kocher et al 2002). Other sets of component causes may exist that can cause sever bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…This is synonymous to stating that for severe bone loss to occur in a smoker, the smoker has to be susceptible. Unfortunately, little is presently known bout what makes a smoker susceptible (Kocher et al 2002). Other sets of component causes may exist that can cause sever bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism of the N‐acetyltransferase (NAT 2) has been shown to be significantly associated with more severe bone loss (53). In addition, smoking may exacerbate the effect of NAT2 on the progression of periodontal disease (74).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Two recent studies have reported that a polymorphism of N -acetyltransferase 2, an enzyme involved in phase II metabolism of xenobiotics, is associated with periodontitis (Kocher et al 2002; Meisel et al 2002); subjects with the slow-acetylating genotype had more severe periodontal disease. These studies were designed to examine whether varying N -acetyltransferase enzyme activity according to N -acetyltransferase polymorphism differentially affected the periodontal risk due to cigarette smoking through the consequent effect on metabolism of smoke-derived xenobiotics.…”
mentioning
confidence: 99%